Biological, Behavioral and Physiological Consequences of Drug-Induced Pregnancy Termination at First-Trimester Human Equivalent in an Animal Model - Camilleri, Christina; Beiter, Rebecca M.; Puentes, Lisett; Aracena-Sherck, Paula; Sammut, Stephen (Frontiers in Neuroscience, 2019)
Given the significant physiological changes that take place during and resulting from pregnancy, as well as the relative absence of such information in relation to pregnancy termination, this study investigated the potential for developing a valid animal model to objectively assess the biological, physiological and behavioral consequences of drug-induced pregnancy termination. Female Long-Evans rats were divided into four groups (n=19-21/group), controlling for drug (mifepristone (50mg/kg/3ml, i.g.)/misoprostol (0.3mg/kg/ml, i.g.) or vehicle (1% Carboxymethylcellulose Sodium/0.2% Tween® 80 suspension, i.g.)) and pregnancy. Drug administration took place on days 12-14 of gestation (days 28-40 human gestational equivalent). Vehicle was administered to the controls on the same days. Parameters measured included rat body weight, food intake, vaginal impedance, sucrose consumption/preference, locomotor activity, forced swim test, and home-cage activity. At the termination of the study, rats were deeply anesthetized using urethane, and blood, brain, and liver were collected for biochemical analysis. Following drug/vehicle administration, only the pregnancy termination group (pregnant, drug) displayed a significant decrease in body weight, food intake, locomotor activity-related behaviors and home-cage activity relative to the control group (non-pregnant, vehicle). Additionally, the pregnancy termination group was the only group that displayed a significant reduction in sucrose consumption/preference during Treatment Week relative to Pre-Treatment Week. Vaginal impedance did not significantly decrease over time in parous rats in contrast to all other groups, including the rats in the pregnancy termination group. Biochemical analysis indicated putative drug- and pregnancy-specific influences on oxidative balance. Regression analysis indicated that pregnancy termination was a predictor variable for body weight, food intake and all locomotor activity parameters measured. Moreover, pertaining to body weight and food intake, the pregnancy termination group displayed significant changes, which were not present in a group of naturally miscarrying rats following pregnancy loss. Overall, our results appear to suggest negative biological and behavioral effects following pregnancy termination, that appear to also be distinct from natural miscarriage, and potential benefits of parity pertaining to fecundity. Thus, our findings indicate the importance for further objective investigation of the physiological and behavioral consequences of medical abortion, in order to provide further insight into the potential implications in humans.